Analysing Crime Waves in Contemporary Nigeria Through the Maqāṣid Al-Sharī‘ah Framework - Sanni, Mubarak (Invest Journal of Sharia & Economic Law, 2025)
The prevalence of crime is a significant socioeconomic challenge in Nigeria. While various studies have examined this issue, none have explored the economic importance of Maqāṣid al-Sharī‘ah (Objectives of Islamic Law) in addressing crime and promoting economic growth. This qualitative study used content analysis and thematic coding to investigate the economic implications of Maqāṣid al-Sharī‘ah for crime management in Nigeria, drawing on primary and secondary sources. The sources included government institutions’ reports, the Qur’ān, Aḥādīth (sayings of Prophet Muḥammad), semi-structured interviews, non-participatory observation, news reports, crime data, textbooks, and journal articles. Using Maqāṣid al-Sharī‘ah as a theoretical framework, this study evaluated Nigerian crime patterns, laws, and policies from an economic perspective. The study found that Nigeria's current system is ineffective in managing crime, particularly in relation to the protection of faith, life, intellect, lineage, and wealth, both in theory and practice, leading to significant economic losses for the country. However, the study revealed that Maqāṣid principles, such as promoting human well-being, preventing harm, and administering justice, have economic importance and can help solve crime waves, ensure economic security, and foster growth and development. The study concluded that incorporating Maqāṣid principles into Nigeria’s socioeconomic and legal systems could effectively address crime prevalence and associated economic losses. This suggests that a comprehensive understanding and implementation of Maqāṣid principles could serve as a model for tackling Nigeria's crime menace and promoting economic growth and development.